2020
DOI: 10.37339/jurpikat.v1i3.414
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Teknologi Deteksi Dini Stunting Sebagai Upaya Peningkatan Status Gizi Anak Di Kelurahan Siwalankerto Kecamatan Wonocolo Surabaya

Abstract: Abstrak: Kegiatan pengabdian masyarakat bertajuk Penerapan Teknologi Deteksi Stunting Dini Sebagai Upaya Peningkatan Status Gizi Anak di Kecamatan Siwalankerto, Kabupaten Wonocolo, Surabaya. Stunting adalah suatu keadaan dimana tinggi badan anak tidak bertambah sesuai dengan usianya, apabila keadaan ini semakin parah akan berdampak pada kematian anak. Program pengabdian masyarakat ini bertujuan untuk meningkatkan kemampuan para ibu kader dalam menggunakan aplikasi untuk menurunkan kejadian stunting. Selain itu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
3
0
2
Order By: Relevance
“…The incidence of stunting is heavily influenced by the behavior of the mother's nutritional intake, even starting when the mother is a teenager, married, and during pregnancy. Inadequate nutritional intake during adolescence often causes anemia in adolescents, which if the adolescent later marries and becomes pregnant, there will be a risk of postpartum hemorrhage, low birth weight, and premature babies [10]. The behavior of prospective mothers and mothers needs to be changed in relation to nutritional intake and to eliminate other factors that influence stunting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of stunting is heavily influenced by the behavior of the mother's nutritional intake, even starting when the mother is a teenager, married, and during pregnancy. Inadequate nutritional intake during adolescence often causes anemia in adolescents, which if the adolescent later marries and becomes pregnant, there will be a risk of postpartum hemorrhage, low birth weight, and premature babies [10]. The behavior of prospective mothers and mothers needs to be changed in relation to nutritional intake and to eliminate other factors that influence stunting.…”
Section: Discussionmentioning
confidence: 99%
“…Thus there can be changes in behavior in toddler mothers. Mothers of toddlers will pay more attention to the child's condition during the growth and development period [10]. Hanieh et al's research on "The Stunting Tool for Early Prevention: development and external validation of a novel tool to predict risk of stunting in children at 3 years of age" concluded that the application of early detection of stunting in infants aged 6 months provides valid predictions of the risk of stunting at 3 [11].…”
Section: Introductionmentioning
confidence: 99%
“…Di dalam konvergensi ini dilakukan upaya-upaya untuk mencegah dan mengurangi gangguan secara langsung meliputi kegiatan ini pada umumnya dilakukan oleh sektor kesehatan, kegiatannya antara lain seperti imunisasi , PMT ibu hamil dan balita, monitoring pertumbuhan balita di Posyandu. Sasaran khusus kelompok 1.000 HPK (Ibu Hamil, Ibu menyusui dan anak 0-23 bulan) (Setiana Andarwulan et al, 2020) Berdasarkan hal tersebut maka Desa Japan ditetapkan sebagai mitra,adapun daerah kelolaan Pengabdian Masyarakat adalah Dusun Prambanan Desa Japan Kecamatan Tegalrejo Magelang. Dusun Prambanan ditetapkan sebagai mitra karena dari prevalensi 24 anak stunting,untuk Prambanan sendiri terdapat 7 anak stunting.…”
Section: Pendahuluanunclassified
“…The solution to this problem is to use an information technology-based website, very appropriate in the era of the covid-19 pandemic to maintain distance and change face-to-face to online [8]. Making a website to solve health problems, has proven to be applicable and can be applied in the community [9].…”
Section: Introductionmentioning
confidence: 99%